Domestic water purification systems and fluoride concentration of home water supply - Yusof, Norashikin; Md Sabri, Budi Aslinie; Bakri, Noor Nazahiah; Md. Bohari, Nor Faezah; Rosli, Nursheila; Suimi, Syaza Nazihah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
The addition of fluoride into the public water supply through regulated and adjusted means, also known as community water fluoridation, has shown to be a very effective public health measure to prevent tooth decay. However, the widespread use of water purifiers to filter the tap water supply, questions have been raised as to whether the fluoride concentration in public water supply has been affected by the water purifier systems that are widely available in today’s market. Objective: To determine the effect of various types of domestic water purifier systems on the fluoride concentration in home water supply. Methods: A total of 100 water samples collected from 25 water purifier systems were included in this study. Results: Reverse osmosis purifier systems showed significant reduction in fluoride concentration at point of use (P=.027). Activated carbon combination water purifier systems showed varying levels of fluoride concentrations at point of use. There was a significant increase in fluoride for the carbon mechanical plus calcium sulphite filter (P=.01) and for the carbon sediment plus nano filter (P=.02) but reduced fluoride concentration for the carbon ceramic and carbon fiber water purifier systems. Conclusions: This study showed that carbon-based water purifier systems may increase or reduced fluoride concentration in water. However, continuous use of water purifiers using reverse osmosis technology can reduce the amount of fluoride and this may give negative implications on oral health